Sociality in the Structure of Modern Literature Criticism - Eleonora Shestakova (Pitannâ Lìteraturoznavstva)
The article raises the problem of sociality and justified in its relations with the verbal and cultural space. It is proved that the social has always been designed to identify the specific interaction of the space of literature and society, time, history, ideology, and everyday life, actualizing their relationship's communication, its creation and its readers, especially their cultural communication network. However, the current literature, for which although still and focus on the inherent social aspects of verbal and cultural space, in contrast to the classical literature turovedeniya oriented at other values of the role and nature of literature, The detection-ruzhivaet insufficient attention and sensitivity to the social, sold directly to the verbal-cultural space. Naturally, this all leads to an interest in social in qualitatively new conditions for the existence of literary theory, but at the same time, the relevance is determined and a sort of “abandonment” of the social in contemporary literary criticism. She, sociality, as it were, is a kind of stumbling block for modern literary criticism, tried to comprehend what had always been an integral and valuable part of the structural integrity under-May and take the words and cultural space, where, according to Berdyaev, “all the threads converge dyatsya central idea of the Logos”. But at the same time, social regarded primarily as a phenomenon of discursive practices, verbal and cultural and philosophical context, the socio-historical sentiment. Sociality breaks and overcomes specific verbal and cultural space, while introducing it in a broad context and entering into it as some additional, conditioned by time and age, bedding. That is one side. But on the other – all this leads to the sociological method in literary criticism, not so much when the actual fabric of the study, especially the verbal, cultural and creative processes, how many times and with the state of their “break” sociality. However, in a qualitatively new ideological and cultural conditions for the existence of modern literary criticism, sociality has not received proper Literary On reflection, rather consistently developed methods. It is this aspect and is relevant to the literature.